2018
DOI: 10.1155/2018/6096483
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Spinal Arteriovenous Malformation: A Rare Cause of Paraplegia in Pregnancy

Abstract: Background Ruptured spinal arteriovenous malformation (AVM) is a rare cause of paraplegia in pregnancy, with only a few case reports describing complications from spinal AVMs during pregnancy in the literature. Case A 32-year-old woman presented at 37 weeks gestation with back pain and rapidly progressive lower limb neurological symptoms. MRI showed a previously undiagnosed spinal AVM at T8. A healthy girl was delivered by caesarean under general anaesthesia to facilitate further investigation. After spinal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[ 3 4 5 ] Similarly Patchana et al and Thiele et al reported motor and organ dysfunction. [ 1 9 ] It has been postulated that the neurological sequelae may be as a result of haemorrhage, mass effect, venous congestion or redistribution of blood. [ 3 10 ] Haemorrhage was identified in the index case and possibly the cause of the neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 4 5 ] Similarly Patchana et al and Thiele et al reported motor and organ dysfunction. [ 1 9 ] It has been postulated that the neurological sequelae may be as a result of haemorrhage, mass effect, venous congestion or redistribution of blood. [ 3 10 ] Haemorrhage was identified in the index case and possibly the cause of the neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that physiological hormonal changes associated with pregnancy, along with compression of venous outflow and augmented intravascular volume make the spinal malformation particularly susceptible to clinical manifestations due to vessel rupture or venous congestion [ 19 ]. The risk of clinical deterioration decreases after delivery and some spinal AVFs may even spontaneously regress [ 20 , 21 ]. In our case, the PMAVF ruptured in the middle of pregnancy but due to the lack of local or myelopathic symptoms, a correct diagnosis was not established at the time of the initial presentation.…”
Section: Discussionmentioning
confidence: 99%